STUDY TO ASSESS THE RISK FACTORS AND CONSEQUENCES OF ALCOHOL CONSUMPTION AMONG ADOLESCENTS - R.AJITHA NANCY RANI (International Journal of Pharma and Bio Sciences, 2016)
Alcoholism is the recent trend among college students. Peer pressure ,stress, depression are some factors that drive these students to practice this social evil. Under intoxication ,consequences are grave. Drunk and driving, road traffic accidents, legal issues, antisocial activities are some of them, that have proved alcoholism a public menace. The present study aimed to assess the risk factors and consequences of alcohol consumption among adolescents. The study was carried out in the selected college of Chennai. Total 60 samples were included for data collection. A questionnaire was prepared comprising of a set of 14 questions covering the main objective of the study. Findings concluded that social gatherings and peer pressure are major factors that prompt students to consume alcohol. Emotional stress and academic stress are other factors. The consequences observed are family problems and health issues. Findings concluded that more than 25% of the subjects consume alcohol due to social gathering, peer pressure, academic stress and emotional stress. Also, more than half of those consuming alcohol are involved in road traffic accidents and other familial problems.